2021
DOI: 10.3390/jpm11121259
|View full text |Cite
|
Sign up to set email alerts
|

Non-Invasive and Surgical Modalities for Scar Management: A Clinical Algorithm

Abstract: Scars can lead to aesthetic and functional impairments. The treatment of scars requires meticulous planning and an individually adapted therapeutic strategy. A conceptual algorithm for scar treatment makes everyday clinical work easier for the practitioner and offers more safety for the patient. Based on a retrospective analysis of 1427 patients who presented for treatment of a variety of scars, we developed an algorithm for scar management and treatment. The treatments are presented using case descriptions. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…While some scars reach complete regeneration, many others undergo pathological tissue repairs, which occur with hypertrophic and keloid scars [ 1 ]. Treatment often involves surgical resection, laser therapy, radiation therapy, physical therapy (i.e., pressure therapy), and medication (i.e., triamcinolone injections) [ 2 5 ]. Currently, a number of animal studies have reported the molecular basis of scar-free healing [ 6 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…While some scars reach complete regeneration, many others undergo pathological tissue repairs, which occur with hypertrophic and keloid scars [ 1 ]. Treatment often involves surgical resection, laser therapy, radiation therapy, physical therapy (i.e., pressure therapy), and medication (i.e., triamcinolone injections) [ 2 5 ]. Currently, a number of animal studies have reported the molecular basis of scar-free healing [ 6 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…PF raw material (170 ± 32 µg) was used to compare Biofiber PF with a no-controlled release system. At scheduled times (2,4,6,8,24,48, and 72 h), 700 µL of PBS was withdrawn from each well and assessed using an HPLC method taken from the literature [19] and adapted for pirfenidone quantification. Briefly, chromatography was carried out using a 1260 Infinity HPLC instrument (Agilent Technologies, Santa Clara, CA, USA) equipped with a Column Guard (C8, 4 × 30 mm) and a reverse phase LUNA column (C8(2), 5 µm, 100 Å, 250 × 4.6 mm) from Phenomenex Ltd. (Phenomenex Ltd., Aschaffenburg, Germany).…”
Section: In Vitro Release Studymentioning
confidence: 99%
“…Therapeutic treatments for HTSs can be categorized based on their method of action [4]. Cryotherapy and ablative laser therapy destroy damaged cells, while surgical treatments like surgical excision and laser surgery remove the fibrotic tissue in an invasive way.…”
Section: Introductionmentioning
confidence: 99%
“…The surgical and non-surgical approaches are the current treatment options for the treatment and management of scars. 5 In detail, surgery is always used to address inadequacies and abnormalities and is particularly useful in patients with functional impairment caused by scar contracture. Nevertheless, the high recurrence rate (more than 40%) has compelled the implementation of adjuvant chemotherapy after surgery.…”
Section: Introductionmentioning
confidence: 99%